Mamah Dede's Communication style in conveying da'wah message in the mama and AA action program in indosiar - Jarosim Simbolon; Tengku Walisyah2 (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2024)
ABSTRACTThis research examines the communication style employed by Mamah Dedeh, a preacher, in delivering sermons utilizing the Tubbs and Moss communication style theory approach. Preachers should be mindful of their communication style when delivering da'wah messages. Utilizing different communication methods has the potential to enhance the significance within an individual's subconscious mind. The chosen communication channel must possess the capacity to preserve the message while also being easily retained by the general population. This study employs a qualitative methodology to analyze Mamah Dedeh's communication style using certain methodologies. The data acquisition technique was conducted by duplicating lectures from YouTube. The collected results indicate that the communication style employed consists of The Controlling Style and The Structuring Style.